USE OF WATER SAVING TECHNOLOGIES IN GARDEN IRRIGATION (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article presents the results of theoretical studies and field trials of the author, conducted in ancestral - economic conditions. Field experiments were carried out on the territory of the Khuzhayakshanba IGC of the Kagan fog of Bukhara region. The technology of garden irrigation with clay water using drip irrigation has been developed. With the introduction of drip irrigation technology in intensive gardens, water resources are saved by 20-60%, mineral fertilizers up to 50% and fuel and lubricants up to 30%, the results of the work are analyzed and presented. In addition, the irrigation regime corresponds to the water needs of plants and excess water is not used, while water evaporation in the soil is insignificant, moisture will collect only near the root system of plants, as a result, water does not disperse throughout the field, due to the small absorption of water by the soil, the level of subsoil water will not rise.